Accuracy analysis of computer-assisted surgery for femoral trochanteric fracture using a fluoroscopic navigation system: Stryker ADAPT®system - Takai, Hirokazu; Murayama, Masatoshi; Kii, Sakumo; Mito, Daisuke; Hayai, Chihiro; Motohashi, Satoru; Takahashi, Tomoki (Injury, 2018)
ADAPT is a fluoroscopic computer-assisted surgery system which intraoperatively shows the distance from the tip of the screw to the surface of the femoral head, tip-to-head-surface distance (TSD), and the tip-apex distance (TAD) advocated by Baumgaertner et al. The study evaluated the accuracy of ADAPT. A total of 55 patients operated with ADAPT between August 2016 and March 2017 were included as subjects. TSD and TAD were measured postoperatively using computed tomography (CT) and X-rays. The intraclass correlation coefficient (ICC) was checked in advance. The error was defined as the difference between postoperative and intraoperative measurement values of ADAPT. Summary statistics, root mean square errors (RMSEs), and correlations were evaluated. ICC was 0.94 [95% CI: 0.90–0.96] in TSD and 0.99 [95% CI: 0.98–0.99] in TAD. The error was −0.35 mm (−1.83 mm to 1.12 mm) in TSD and +0.63 mm (−5.65 mm to 4.59 mm) in TAD. RMSE was 0.63 mm in TSD and 1.53 mm in TAD. Pearson’s correlation coefficient was 0.79 [95% CI: 0.66–0.87] in TSD and 0.83 [95% CI: 0.72–0.89] in TAD. There were no adverse events with ADAPT use. ADAPT is highly accurate and useful in guiding surgeons in properly positioning the screws.